The Role of Green Marketing and Brand Image on Purchase Decisions of Aqua Reflection - Fatma Yulinda Ariani; R Amalina Dewi Kumalasari (PINISI Discretion Review, 2023)
In addition to the increasingly fierce and competitive competition, bottled water companies in Indonesia face environmental challenges, such as processing plastic waste. Responding to these challenges, packaged water companies innovate by providing environmentally friendly packaging and implementing Green Marketing to create a positive image and attract customers. This study aims to show the relationship between green marketing on brand image and consumer decisions on Aqua Reflection. This study involved 100 respondents who consumed Aqua Reflection, a drinking water product from Aqua that uses glass bottles. The analysis technique used is path analysis with Partial Least Squares (PLS). The results show that green marketing affects the brand image, green marketing directly affects purchasing decisions, and the brand image directly affects buying decisions. Green marketing indirectly affects purchasing decisions through brand image.